2021
DOI: 10.1002/iid3.415
|View full text |Cite
|
Sign up to set email alerts
|

The effects of secreted aspartyl proteinase inhibitor ritonavir on azoles‐resistant strains of Candida albicans as well as regulatory role of SAP2 and ERG11

Abstract: Background Candida albicans, the main human fungal pathogen, can cause fungal infection and seriously affect people's health and life. This study aimed to investigate the effects of ritonavir (RIT) on C. albicans and the correlation between SAP2 as well as ERG11 and drug resistance. Results Secreted aspartyl proteinases (Saps) activities and pathogenicity of C. albicans with different drug resistance were measured. M27‐A4 broth microdilution method was used to analyze the drug sensitivity of RIT combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, upon the addition of fluconazole, both groups showed increased Erg11 expression. 72 There were statistically significant difference concerning the association of proteinase activities and Erg 11 gene expression among fluconazole resistance Candida isolates. This was in accordance with Feng et al, 2021 72 who reported that the expression of secreted aspartyl proteinase 2 (SAP2) and ERG11 was significantly higher in the resistant strains compared with the sensitive strains, and there was a positive liner correlation between SAP2 and ERG11 messenger RNA expression.…”
Section: Discussionmentioning
confidence: 92%
“…However, upon the addition of fluconazole, both groups showed increased Erg11 expression. 72 There were statistically significant difference concerning the association of proteinase activities and Erg 11 gene expression among fluconazole resistance Candida isolates. This was in accordance with Feng et al, 2021 72 who reported that the expression of secreted aspartyl proteinase 2 (SAP2) and ERG11 was significantly higher in the resistant strains compared with the sensitive strains, and there was a positive liner correlation between SAP2 and ERG11 messenger RNA expression.…”
Section: Discussionmentioning
confidence: 92%
“…Genetic mutations are also associated with cross-resistance. For example, C. albicans isolates containing the A516P mutation in ERG11 exhibit an upregulated ERG11 expression and a notable cross-resistance to fluconazole, itraconazole, and voriconazole [ 12 ].…”
Section: Antifungal Resistances Mediated By Genetic Mutationsmentioning
confidence: 99%
“…All the primers used in the present study are listed in Table 1 and had been commercially synthesized (Shanghai Sangon Biotech). [20][21][22][23] Yeast-DNA materials were carefully extracted as PCR templates with UNIQ-10 Column Yeast Plasmid Preps Kit (Shanghai Sangon Biotech), and PCR amplifications were conducted with an Applied Biosystems 7500 DNA analyzer (Thermo Fisher Scientific). The PCR parameters included 5 minutes at 94°C for initial denaturation, 32 cycles (30 s at 94°C for denaturation, 90 s at 50°C for annealing, and 90 s at 72°C for elongation), and 10 minutes at 72°C for last elongation.…”
Section: Azole-resistance Gene Sequencing and Homologous 3d-structure...mentioning
confidence: 99%